2021
DOI: 10.1002/mame.202170010
|View full text |Cite
|
Sign up to set email alerts
|

A Structure‐Properties Relationship Study of Self‐Healing Materials Based on Styrene and Furfuryl Methacrylate Cross‐Linked via Diels–Alder Chemistry

Abstract: This study provides some important tools for the design of materials characterized by thermally reversible behavior, which find usually application as self-healing thermosets, coatings, or adhesives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Furan/maleimide chemistry has been used to crosslink rubbers, [ 14,76,78 ] poly sacharides, [ 5,10,13 ] carbon‐nanotubes, [ 79 ] poly ketones, [ 47 ] polyacrylates, [ 80 ] and poly ethers [ 55 ] to yield recyclable thermosets. The studies discussed in this section cover solely systems for which the kinetics were analyzed, The collected data are listed in Table 3 .…”
Section: Effect Of Architecture On Reported Kineticsmentioning
confidence: 99%
“…Furan/maleimide chemistry has been used to crosslink rubbers, [ 14,76,78 ] poly sacharides, [ 5,10,13 ] carbon‐nanotubes, [ 79 ] poly ketones, [ 47 ] polyacrylates, [ 80 ] and poly ethers [ 55 ] to yield recyclable thermosets. The studies discussed in this section cover solely systems for which the kinetics were analyzed, The collected data are listed in Table 3 .…”
Section: Effect Of Architecture On Reported Kineticsmentioning
confidence: 99%
“…Hence, they can lead to thermoreversible crosslinked materials, which can be used as thermoresponsive materials. Accordingly, RDRP copolymers containing FMA repeat units have been widely investigated for applications such as self‐healing materials, [ 129–132 ] responsive nanoparticles, [ 133 ] smart hydrogels, [ 134 ] and surfaces. [ 135 ] Representative examples are self‐healable materials based on well‐defined ABA triblock copolymers containing reactive PFMA end blocks.…”
Section: Well‐defined Poly(meth)acrylates Based On Lignocellulosic Su...mentioning
confidence: 99%
“…CANs operate on the principle of dynamic covalent chemistry, , where covalent bonds can exchange over time, as opposed to supramolecular chemistry, where noncovalent bonds can exchange. Examples of dynamic covalent bonds used in CANs are the Diels–Alder reaction, , N,S-acetals, nucleophilic transalkylation reactions, imines, disulfides, esters, , vinylogous urethanes, , diketoamines, , acylsemicarbazides, , and boronic esters. In this study, we chose to use the well-known boronic ester bond, on which we reported previously, , for the formation of dynamically cross-linked networks. , …”
Section: Introductionmentioning
confidence: 99%